Improving Compliance with Scheduled Dates in Calibration Services Applying Six Sigma - Enciso Acuña, Zenaida Virginia (2020)
This article is the result of the application of Six Sigma methodology to improve compliance with scheduled dates in services performed by a calibration laboratory at the customer’s facilities. Through its five phases, Six Sigma methodology makes it possible to define the problem in a specific and quantitative way, measuring the performance of the affected process, identifying and analyzing the root causes, as well as establishing the actions to overcome problems and the controls to maintain the improvements. In this way, the laboratory increases the compliance with scheduled dates from 56.2% to 70.3%, as well as the level of customer satisfaction from 72.3% to 84.6%.